Methane Oxidation in three Swedish Forest Soils - Osam, Kwesi Idun (2012)
Aerated soils are the largest sinks of atmospheric methane on the Earth’s surface. Methane removal from the atmosphere is performed through oxidation by microorganisms (methaneoxidising bacteria) in the soil. Methanotrophic bacteria utilise methane (single-carbon compound) as their main carbon and energy source, but some groups have been found to grow on different multi-carbon compounds. This thesis investigated the influence of soil methanotrophs on the kinetics of methane oxidation in Swedish forest soils and the effect of the tree species Scots pine (Pinus sylvestris), Norway spruce (Picea abies) and birch (Betula pendula) on methane consumption rates. Soil samples were collected from the study area Vipängen (Ultuna), which is classified as a Dystrocryept with its O horizon between 0-5 cm, A horizon 5-20 cm and B horizon 20-40 cm. The potential effect of other multi-carbon substrates (acetate, vanillic acid and guaiacol) that could be expected to enhance the oxidation rate of atmospheric methane was also examined. The results showed that the methanotrophs at the study site were high-affinity species with Vmax values ranging between 4.3 and 11.0 nmol CH4 g-1d.w. hr-1 and Km ranging between 7.4 and 185.5 nmol g-1d.w. Type of tree species which is proposed to have a strong influence on the methane sink, clearly did so in this incubation experiment. Consumption in soil samples from a birch stand displayed the highest consumption rate, followed by spruce and pine for all four different initial concentrations of methane tested (4.5, 7, 14.1 and 45.1 ppmv). Evaluation of the effects of acetate, vanillic acid and guaiacol on methane consumption rates in the Swedish forest soils studied showed that only addition of acetate yielded a substantial effect, demonstrating that methanotrophs are not just limited to single-carbon bonds. Further studies on the effects of different multi-carbon compounds on the growth of some methanotrophic species (increased oxidation) will provide in-depth knowledge of the factors governing methane fluxes between the atmosphere and the soil.